Safety and Feasibility of Additional Tumor Debulking to First‐Line Palliative Combination Chemotherapy for Patients with Multiorgan Metastatic Colorectal Cancer. (16th June 2020) - Gootjes, Elske C.; van der Stok, Eric P.; Buffart, Tineke E.; Bakkerus, Lotte; Labots, Mariette; Zonderhuis, Barbara M.; Tuynman, Jurriaan B.; Meijerink, Martijn R.; van de Ven, Peter M.; Haasbeek, Cornelis J.A.; ten Tije, Albert J.; de Groot, Jan‐Willem B.; et al.
Abstract: Introduction: Local treatment of metastases is frequently performed in patients with multiorgan metastatic colorectal carcinoma (mCRC) analogous to selected patients with oligometastatic disease for whom this is standard of care. The ORCHESTRA trial (NCT01792934) was designed to prospectively evaluate overall survival benefit from tumor debulking in addition to chemotherapy in patients with multiorgan mCRC. Here, we report the preplanned safety and feasibility evaluation after inclusion of the first 100 patients. Methods: Patients were eligible if at least 80% tumor debulking was deemed feasible by resection, radiotherapy and/or thermal ablative therapy. In case of clinical benefit after three or four cycles of respectively 5‐fluorouracil/leucovorin or capecitabine and oxaliplatin ± bevacizumab patients were randomized to tumor debulking followed by chemotherapy in the intervention arm, or standard treatment with chemotherapy. Results: Twelve patients dropped out prior to randomization for various reasons. Eighty‐eight patients were randomized to the standard ( n = 43) or intervention arm ( n = 45). No patients withdrew after randomization. Debulking was performed in 82% ( n = 37). Two patients had no lesions left to treat, five had progressive disease, and one patient died prior to local treatment. In 15 patients (40%) 21 serious adverse events related to debulking were reported. Postoperative mortality was 2.7% ( n = 1). After debulking chemotherapy was resumed in 89% of patients. Conclusion: Tumor debulking is feasible and does not prohibit administration of palliative chemotherapy in the majority of patients with multiorgan mCRC, despite the occurrence of serious adverse events related to local treatment. Implications for Practice: This first prospective randomized trial on tumor debulking in addition to chemotherapy shows that local treatment of metastases is feasible in patients with multiorgan metastatic colorectal cancer and does not prohibit administration of palliative systemic therapy, despite the occurrence of serious adverse events related to local treatment. The trial continues accrual, and overall survival (OS) data and quality of life assessment are collected to determine whether the primary aim of >6 months OS benefit with preserved quality of life will be met. This will support evidence‐based decision making in multidisciplinary colorectal cancer care and can be readily implemented in daily practice. Abstract : The ORCHESTRA trial was designed to prospectively evaluate overall survival benefit from tumor debulking in addition to chemotherapy in patients with multi‐organ metastatic colorectal cancer. This article reports the preplanned safety and feasibility evaluation after inclusion of the first 100 patients.